Hotspot Management Training Using Mikrotik RouterBoard to Support Independent Internet Access for the Community - Setiadi, Dedi; Syahri, Riduan; Febriansyah; Gusmaliza, Debi; Masdalipa, Risnaini (LKP KARYA PRIMA KURSUS, 2026)
Currently, the internet has become one of the basic needs for society, one of which is in the field of education. Where many students or college students are constrained in participating in learning or searching for materials due to internet access constraints, so hotspot creation training is needed. The creation of this hotspot aims to ensure that all activities that require internet access can run smoothly. The training is carried out through community service activities as a solution to problems that occur in the community. The stages of implementing this community service consist of 4 (four) stages, namely the first stage of preparation by conducting surveys and interviews, the second stage of training implementation is carried out by delivering materials and practicing hotspot creation, the third stage is an evaluation by giving questionnaires to participants to determine the understanding of each participant, and the fourth stage is making reports and publications as outputs of community service activities. Based on the evaluation that has been carried out, it is known that the level of understanding and knowledge of the training participants has increased significantly. Before participating in the training, only 50% of participants knew about computer networks, increasing to 95%. Before participating in the training, only 5% of participants had ever created a hotspot with a Mikrotik router board, increasing to 90%. Before participating in the training, only 5% of participants were able to configure Mikrotik, increasing to 90%. Before the training, only 5% of participants were able to create a hotspot using a Mikrotik router board, increasing to 80%. Before the training, only 50% of participants understood the functions of the internet and hotspot, increasing to 95% after the training